Phenotypic and metabolic adaptations of Rhodococcus cerastii strain IEGM 1243 to separate and combined effects of diclofenac and ibuprofen - Elena Tyumina; Elena Tyumina; Grigory Bazhutin; Grigory Bazhutin; Nadezhda Kostrikina; Vladimir Sorokin; Andrey Mulyukin; Irina Ivshina; Irina Ivshina (Frontiers in Microbiology, 2023)
IntroductionThe increasing use of non-steroidal anti-inflammatory drugs (NSAIDs) has raised concerns regarding their environmental impact. To address this, understanding the effects of NSAIDs on bacteria is crucial for bioremediation efforts in pharmaceutical-contaminated environments. The primary challenge in breaking down persistent compounds lies not in the biochemical pathways but in capacity of bacteria to surmount stressors.MethodsIn this study, we examined the biodegradative activity, morphological and physiological changes, and ultrastructural adaptations of Rhodococcus cerastii strain IEGM 1243 when exposed to ibuprofen, diclofenac, and their mixture.Results and DiscussionOur findings revealed that R. cerastii IEGM 1243 exhibited moderate biodegradative activity towards the tested NSAIDs. Cellular respiration assay showed higher metabolic activity in the presence of NSAIDs, indicating their influence on bacterial metabolism. Furthermore, catalase activity in R. cerastii IEGM 1243 exposed to NSAIDs showed an initial decrease followed by fluctuations, with the most significant changes observed in the presence of DCF and the NSAID mixture, likely influenced by bacterial growth phases, active NSAID degradation, and the formation of multicellular aggregates, suggesting potential intercellular synergy and task distribution within the bacterial community. Morphometric analysis demonstrated alterations in size, shape, and surface roughness of cells exposed to NSAIDs, with a decrease in surface area and volume, and an increase in surface area-to-volume ratio (SA/V). Moreover, for the first time, transmission electron microscopy confirmed the presence of lipid inclusions, polyphosphates, and intracellular membrane-like structures in the ibuprofen-treated cells.ConclusionThese results provide valuable insights into the adaptive responses of R. cerastii IEGM 1243 to NSAIDs, shedding light on the possible interaction between bacteria and pharmaceutical compounds in the environment.